The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1254/jphs.fp0040203
|View full text |Cite
|
Sign up to set email alerts
|

Prior Antagonism of Endothelin-1A Receptors Alleviates Circulatory Shock and Cerebral Ischemia During Rat Heatstroke

Abstract: Abstract. In this study, we investigated the acute hemodynamic effects of an infusion of the endothelin-1 (ET-1)-A-selective receptor antagonists BQ-610 and BQ-123 in heatstroke rats with circulatory shock and cerebral ischemia. Heatstroke was induced by putting the anesthetized adult Sprague-Dawley rats into an ambient temperature of 42°C. The moment in which the mean arterial pressure dropped irreversibly from the peak for an extent of 25 mmHg was taken as the onset of heatstroke. The interval between initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Indeed, both present and previous (26,27) results have shown that both cerebral ischemia and injury that occurred during heatstroke are associated with an increased production of glycerol, lactate / pyruvate ratio, and glutamate in the brain. Our results further demonstrated that PO 2 in the rat brain was greatly reduced after the onset of heatstroke.…”
Section: Discussionmentioning
confidence: 49%
“…Indeed, both present and previous (26,27) results have shown that both cerebral ischemia and injury that occurred during heatstroke are associated with an increased production of glycerol, lactate / pyruvate ratio, and glutamate in the brain. Our results further demonstrated that PO 2 in the rat brain was greatly reduced after the onset of heatstroke.…”
Section: Discussionmentioning
confidence: 49%
“…Animals, under urethane anesthesia, were positioned in a stereotoxic apparatus (model 1460; David Kopf Instruments, Tujunga, CA, USA) to insert a probe for measurement of local CBF in the striatum (5). A 100-µm-diameter thermocouple and two 230-µm fibers were attached to the oxygen probe.…”
Section: Cbf Monitoringmentioning
confidence: 99%
“…Intestinal mucosal permeability to endotoxin increases in heat stressed rats (4) and lead to production of inflammatory cytokines that induce release of nitric oxide (NO) (3) and endothelins (5). Both pyrogenic cytokines and endothelin-derived factors can precipitate arterial hypotension, hyperthermia, and cerebral ischemia during heatstroke (5 -7).…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of NO may contribute to the splanchnic vasodilation that precedes vascular collapses with heatstroke. Our previous results have further shown that in addition to overproduction of NOx in brain, decreased cardiac output (due to decreased total peripheral vascular resistance and stroke volume), intracranial hypertension, and cerebral ischemia and hypoxia, and hyperthermia occur during heatstroke in the rat (10,11,21). Our previous findings have also shown that accumulation of large amounts of reactive oxygen species in various organs including the kidney and the brain is associated with hyperthermia, arterial hypotension, and cerebral ischemia and injury during heatstroke (22,23).…”
Section: Discussionmentioning
confidence: 70%
“…This alteration allows leakage of endotoxins and increases production of inflammatory cytokines that induce release of NO and endothelins (10,11). Both pyrogenic cytokines can interfere with normal thermoregulation, thereby precipitating arterial hypotension, hyperthermia, and heatstroke (1).…”
Section: Introductionmentioning
confidence: 99%